The public public school a redevelopment of the Pinaglabanan Elementary School Complex into a school-public space and park mixed-use development. - Jetigan, John Michael P.
The inevitable problem of land scarcity in cities has led to shortages in classrooms and school facilities, besides the lack of space for parks and public services. In the small city of San Juan, public schools have adapted by holding double shifts and building-up school sites, maximizing lot areas. In the process of densifying these school sites which are typically prime land that are well located and connected yet only utilized seven to eight hours a day, five times a week, it can be asked how can these be further maximized and reclaimed to not just benefit the school but also the entire community and by extension, the city "Can we make the public school more public?" Working with the Pinaglabanan Elementary School, situated across the historic Pinaglabanan Shrine within the civic core of San Juan, the Public Public School redeveloped the existing elementary school, integrated a new campus for the city's only public senior high school, provided a more visible, accessible home to the city library, opened the site to improve mobility and increase commercial opportunities, and added a variety of time-shared and elevated public spaces. This was done with the help of context analysis and thoughtful zoning and programming to connect users, spaces, and context; integrated function; and at times, separate areas while keeping in mind beneficial relationships that could be enhanced and conflicts that needed to be addressed. In the end, the Public Public School aims to be an initial exploration of the mixed-use public school as a part of the city.